FUNCTIONAL RESULTS OF TYMPANOPLASTY WITH DIFFERENT VARIANTS OF THE SOUND CONDUCTING DEVICE RECONSTRUCTION OF THE MIDDLE EAR - Srebnyak, I.A.; Shevchenko, T.O.; Pedachenko, A.Ye. (World of Medicine and Biology, 2021)
Presently the surgical treatment and rehabilitation of patients with chronic supputative middle ear otitis remains importantal in modern otiatry. The purpose of our work was to study the functional results of hearing improving operations with the use of artificial, biological and combined prostheses and assessment of the clinico–roetgenological conditions for their use in the patients with middle ear surgery pathology. An optimal length of the partial prosthesis has been established for reconstruction of the hearing bones depending on the timpanoplastia variant. After reconstructive operations performed in the patients with chronic suppurative otitis media there was an improvement of the hearing function in the sound–conducting apparatus in all study groups during the nearest 3–month period after surgery (р
Keywords: chronic suppurative otitis media; partial ossicular prosthesis; total ossicular prosthesis; timpanoplasty; chainlet of auditory ossicles